Effect of prostaglandin 15(R) 15 methyl-E2 methyl ester on aspirin and taurocholic acid-induced gastric mucosal haemorrhage in rats. Issue 1 (January 1976) - Carmichael, H A; Nelson, L; Russell, R I; Chandra, V; Lyon, A; Cochran, K M
Abstract : The effect of orally administered prostaglandin 15(R)15 methyl-E2 methyl ester on aspirin and taurocholic acid-induced gastric mucosal haemorrhage has been studied in rats. The incidence of haemorrhage induced by aspirin (26-7 mM), 64 mg/kg, together with taurocholic acid (2-5 mM), was significantly reduced from 53-6% to 19-5% by the addition of the prostaglandin (9-9 muM), P less than 0.01. The incidence of haemorrhage induced by aspirin alone (53-3 mM), 128 mg/kg, was significantly reduced from 80% to 20% by the addition of prostaglandin (9-9 muM), P less than 0.002. These results indicate the possible use of synthetic prostaglandins in the prevention of aspirin-induced gastric pathology.